SOSIALISASI PENCATATAN PEMBUKUAN SEDERHANA BAGI PELAKU UMKM DI DESA ABUAN KECAMATAN SUSUT KABUPATEN BANGLI - A. A. Ayu Shinta Restiani; Irzaqi Maulana Rizal; I Made Artana; Made Mulia Handayani; I Made Artayasa; I Ketut Satria Wiradharma Sumertajaya; Gede Sumarda (LPPM Universitas Bina Bangsa, 2024)
Abuan Village, Susut District, Bangli Regency is a village where most of the residents are SME (Micro Small Medium Enterprises). The main problem faced by SME actors in Abuan Village is the problem of limited insight and knowledge possessed related to simple bookkeeping records in their MSME businesses. Therefore, the purpose of the service of Group 11 KAT Ngurah Rai University is to help improve the ability of SME actors to record books that are simple and easy to understand. The method used in the implementation of community service in Abuan Village is the approach method by conducting door-to-door socialization regarding recording simple financial statement bookkeeping to MSME actors around Abuan village, Susut District, Bangli Regency. The result of the activities carried out by Group 11 KAT of Ngurah Rai University is that business actors state that implementing bookkeeping in businesses has a positive effect and is very important to be used for businesses to know how to calculate business profit or loss and measure their business capabilities. For this reason, this activity is expected to contribute to how to compile books between income and expenditure, and it is expected that MSME actors can practice directly so that it can facilitate the process of recording cash flow and performance obtained by SME